(untitled) (Journal of Partial Differential Equations, 2014)
" Under a non-Lipschitz condition being considered as a generalized case of Lipschitz condition, the existence and uniqueness of mild solutions to neutral stochastic functional differential equations driven by fractional Brownian motion with Hurst parameter 1\/2 2039 H 2039 1 are investigated. Some known results are generalized and improved."